The Defiant: The Valiant Series #2 - Livingston, Lesley (New York : Razorbill, an imprint of Penguin Random House LLC, 2018)
When Fallon and her fellow gladiatrices are thrust into a vicious conflict with a rival gladiator academy, the only thing that might save them is a tribe of long-forgotten mythic Amazon warriors.
Keywords: Caesar, Julius -- Juvenile fiction; Caesar, Julius -- Fiction; Caesar, Julius -- Fiction; Gladiators -- Fiction; Amazons -- Fiction; Princesses -- Fiction; Gladiators -- Fiction; Princesses -- Fiction; Rome -- History -- Empire, 30 B.C.-476 A.D. -- Fiction; Rome -- History -- Fiction